Evaluating gas generation and preservation of the Wufeng-Longmaxi Formation shale in southeastern Sichuan Basin, China: Implications from semiclosed hydrous pyrolysis. (July 2021) - Ma, Zhongliang; Tan, Jingqiang; Zheng, Lunju; Shen, Baojian; Wang, Zhanghu; Shahzad, Asim; Jan, Irfan U.; Schulz, Hans-Martin
Abstract: The oil expulsion efficiency of organic-rich shale during peak oil generation influences the generation of shale gas at high maturity, while the gas expulsion and loss efficiency affect the enrichment and preservation of shale gas. Two series of semiclosed hydrous pyrolysis experiments were performed under in situ geological conditions on Devonian shale sample as comparable analogue to evaluate the generation and preservation potential of shale gas in the Wufeng-Longmaxi Formation shale in the southeastern Sichuan Basin. The results indicate that the maximum oil expulsion efficiency of the Wufeng-Longmaxi shale is 68.8%. Retained oil is the main source of shale gas formed at high maturity. When the value of equal vitrinite reflectance (EqVRo) reaches 3.18%, the total gas generative potential from the retained oil and kerogen is 214.06 mL/g TOC, while that from kerogen is only 69.84 mL/g TOC. Overall, retained oil-formed gas at high maturity (EqVRo >1.30%) accounts for 60.82%–68.26% of the total gas, and the kerogen-formed gas is between 31.74% and 39.18% of the total gas. Based on the analysis of the JY2 well, Wufeng-Longmaxi shales with TOC contents >1.5% lose 60–80% of the total gas, while shales with TOC contents <1.5% lose 70–100% of the total gas. A TOC content of 1.5% can still meet the 2 m 3 /t gas content as evaluation standard for selecting favorable marine shale gas play areas in China. Highlights: Semi-closed hydrous pyrolysis was used for gas evaluation of the Wufeng-Longmaxi shale. The maximum oil expulsion efficiency is 68.8%. The total gas generative potential is 214.06 ml/gTOC. Shales with TOC >1.5% lost 60～80% of the generated gas. Expulsion efficiency, gas expulsion, and loss efficiency are critical in shale gas evaluation.